Readers' Selective Recall of Source Features as a Function of Claim Discrepancy and Task Demands. Issue 5 (18th August 2018) - Saux, Gaston; Ros, Christine; Britt, M. Anne; Stadtler, Marc; Burin, Debora I.; Rouet, Jean-François
ABSTRACT: In two experiments, undergraduate students read short texts containing two embedded sources that could either agree or disagree with each other. Participants' memory for the sources' identity (i.e., occupation) and features (i.e., the source's access to knowledge and the source's physical appearance) was examined as a function of the consistency of their assertions. In Experiment 1 ( n = 64), sources were described with only one feature (knowledge or appearance), whereas in Experiment 2 ( n = 62), each source was described with both features. Experiment 1 additionally tested the influence of two different tasks during reading (an evaluation of sources' knowledgeability vs. an evaluation of sources' age). Consistent with our predictions, knowledge evaluations (Experiment 1) and discrepant claims (Experiments 1 and 2) enhanced memory for sources and their features. Experiment 2 also showed that when both types of features were available, discrepant claims selectively benefited memory for a source's knowledgeability over appearance.